3D direct laser writing of Petabyte Optical Disk. (August 2015) - Pavel, E.; Jinga, S.I.; Vasile, B.S.; Dinescu, A.; Trusca, R.; Tosa, N.
Abstract: We report novel results for 3D recording of an optical disk with ultra-high density. Multilayer 5 nm nanomarks were experimentally obtained by using fluorescent photosensitive glass-ceramics and an optical head with λ =650 nm and NA=0.60. The distance between adjacent 5 nm nanomarks has been reduced to 10 nm. Ultra-high density optical data is recorded by focusing laser beam of a CW laser diode operating at low power ( P max =10 mW). Highlights: 3D recording of nanostructures by using low power CW lasers. 5 nm structures were obtain by Quantum Multiphoton Confinement (QMC) effect. Data storage capacity over 1 PB has been demonstrated. Petabyte Optical Disk could be a solution for long term data archiving. TEM and SEM were used to analyze the nanostructures.